Strengthening Movement Ideology through The Management of Campus Da'wah Institutions - Muhdi, Muhdi; Hamdan, Hamdan; Murdan, Murdan (JURNAL AL-TANZIM, 2023)
This study explores management strategies and practices carried out by campus dakwah institutions in building a solid movement ideology within one of the public tertiary institutions in Banjarmasin. This research uses a descriptive qualitative approach. The data collection technique was done through participatory observation, in-depth interviews and documentation. Data analysis was done through data reduction, visualization, and conclusion. The study results show that managing campus da'wah institutions involves various strategies that focus on developing a solid movement ideology, namely, partnership cooperation with lecturers, preparation of study materials for campus da'wah institutions, mentoring and strengthening of ideological foundations. The management of campus dakwah institutions plays a significant role in building the movement's ideology at public universities in Banjarmasin. Management strategies and practices carried out by campus da'wah institutions contribute to strengthening movement ideology and increasing the effectiveness of da'wah on campus and in the surrounding community. This research provides guidance and insight for campus da'wah institutions in developing a strong and sustainable movement ideology.